2006
DOI: 10.1007/s00277-006-0228-8
|View full text |Cite
|
Sign up to set email alerts
|

Teaching hematology to second year medical students: results of a national survey of hematology course directors

Abstract: Increasing clinical productivity expectations at academic medical centers and new faculty effort reporting requirements for NIH-supported investigators challenge the tradition of faculty volunteerism for medical student teaching. To better define the structure, content, and financial support of second year medical school hematology courses nationwide, we mailed a survey to the hematology course directors at 85 of the 125 accredited US medical schools. The 58 course directors who returned the survey represent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Educators in other specialties have noted similar findings. In a survey of hematology course leaders performed by the American Society of Hematology, 45% noted difficulty recruiting faculty to teach, and many voiced frustration regarding the lack of academic reward for teaching (4). Two potential sources of bias, however, may have led to underestimation of compensation in the present survey.…”
Section: Educational Strategy Commentsmentioning
confidence: 73%
See 1 more Smart Citation
“…Educators in other specialties have noted similar findings. In a survey of hematology course leaders performed by the American Society of Hematology, 45% noted difficulty recruiting faculty to teach, and many voiced frustration regarding the lack of academic reward for teaching (4). Two potential sources of bias, however, may have led to underestimation of compensation in the present survey.…”
Section: Educational Strategy Commentsmentioning
confidence: 73%
“…and G.A.H., who are both course leaders in kidney pathophysiology. Content was validated by a subgroup of the ASN Workforce Committee as well as analysis of a similar survey conducted by the American Society of Hematology (4). At the authors' institutions, the survey was determined to be exempt from additional review, and a waiver for consent was granted from the institutional review board (G.A.H.)…”
Section: Methodsmentioning
confidence: 99%
“…This trend of increased digital methods and decreased laboratory time is echoed by surveys of hematology course directors (Broudy and Hickman, 2007) and histology and anatomy course directors (Bloodgood and Ogilvie, 2006;Drake et al, 2009). At MMS, both virtual microscopy and projected images of histopathology are now used as an adjunct teaching method in a number of year one and two organ specific courses, including hematology.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of hematology course directors found that projection-based learning was widely used by course directors, and laboratory skills (20%) and microscopy (60%), were used less commonly (Broudy and Hickman, 2007). A recent survey of hematology course directors found that projection-based learning was widely used by course directors, and laboratory skills (20%) and microscopy (60%), were used less commonly (Broudy and Hickman, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, however, the students questioned the usefulness of some of the matters presented for their future practice and the lecturers felt that they had too little evidence to support a credible answer. The research literature on undergraduate haematology curriculum is minimal: a single study (Broudy & Hickman 2007) surveyed the undergraduate programmes at medical schools in the USA and found a great diversity of content and teaching methods among them. By contrast, the postgraduate haematology training is oriented by model curricula, originating from the American Society of Haematology and the European Haematology Association.…”
Section: An Application: Delphi As a Methods Of Inquiry Into The Relevmentioning
confidence: 99%